Assessment of Pollution Level and Its Impacts in the Shatt Al-Arab River in Basra Province, Iraq - Saad M. Potrous (Research Advances in Environment, Geography and Earth Science Vol. 8, 2024)
Water pollution or water pollution is any physical or chemical change in the quality of water, directly or indirectly, that negatively affects living organisms, or makes the water unsuitable for the required uses. A reviewed the Aerial Photographs of Google Maps taken on the Shatt al-Arab river in Basra Province, Iraq, which clearly showed the presence of pollution in the river waters. Three regions (1,2,3) of the river are used for determining the pollution in these regions. Chemical analysis of the three regions samples (1,2,3) was conducted in the laboratories of the University of Basra for the purpose of measuring the total dissolved salts (TDS), elemental Lead (Pb), and Sulfate compounds (SO4). The results confirmed an increase in the total dissolved salts (TDS) in the waters of the Shatt al-Arab towards the south, where the river waters meet with the Gulf waters. The results also confirmed an increase in Lead (Pb) concentrations in regions (2 and 3) to (0.8 mg/l), compared to the World Health Organization’s (WHO) international limit value of (0.05 mg/k). As sulfate (SO4) compounds are recorded at a value of (750 mg/l) in the region (3) of the river, compared to the international limit value of the World Health Organization (WHO), which is (400 mg/l). These results correspond to the statistics by the Basra Province Heath Directorate, which showed the increase in the proportion of casualties among the population of the province of Basra in the regions (2 and 3) adjacent to the Shatt Al-Arab river, such as the city center, Abi- AlKhaseb and Shatt Al Arab from the rest of the regions causing water pollution and the spread of E. coli causing diarrhea and intestinal colic with 50% of cases which was admitted to Basra hospitals.